A state-dependent critical state model for methane hydrate-bearing sand. (May 2016) - Shen, J.; Chiu, C.F.; Ng, C.W.W.; Lei, G.H.; Xu, J.
Abstract: Methane hydrate exists in the pores of methane hydrate-bearing sand (MHBS) and is considered to be a potentially significant source of methane and thus energy for mankind. However, before conducting a large-scale extraction of methane from MHBS, it is crucial to simulate the mechanical behaviour of MHBS and evaluate its stability during drilling and methane production. In this paper, a state-dependent critical state model for MHBS is presented. The critical state of MHBS is discussed, and critical state line formulations are introduced as functions of hydrate saturation. A simple nonlinear bonding and linear debonding law is incorporated considering the cementing mechanism of hydrate. A modified state-dependent dilatancy is proposed to account for the effects of stress level, internal state (density), bonding strength and hydrate saturation. Determination of the model parameters is described in detail. The proposed model is employed to predict results of drained triaxial compression tests on MHBS. Satisfactory performance is demonstrated, i.e., the model can adequately capture the stress–strain and volume change behaviours of MHBS over a wide range of hydrate saturations, confining pressures and densities using a unified set of parameters.